2021
DOI: 10.1111/aos.15051
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial–mesenchymal transition‐related serum markers ET‐1, IL‐8 and TGF‐β2 are elevated in a Finnish wet age‐related macular degeneration cohort

Abstract: It has been hypothesized that epithelial-mesenchymal transition (EMT) may occur in the retinal pigment epithelium of advanced stage age-related macular degeneration (AMD). Various serum and plasma growth factors and inflammatory mediators have been linked to AMD. We were interested in finding out whether systemic levels of EMT-associated markers were altered in the serum of wet AMD patients. Serum biomarkers associated with the various pathological processes of AMD may present an avenue towards identifying and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 105 publications
1
3
0
Order By: Relevance
“…VEGF-A serum levels, as well as VEGFA SNPs, are widely studied in AMD patients. While we did not find any statistical differences in VEGF-A serum levels between the exudative AMD patients and controls, we confirmed results from several other studies which included total AMD patients or only exudative AMD patients, consisting of 27 to 71 samples per group in different populations [53][54][55][56][57][58][59][60]. Further studies revealed significantly elevated VEGF-A levels in exudative AMD patients compared to controls [61,62].…”
Section: Discussionsupporting
confidence: 88%
“…VEGF-A serum levels, as well as VEGFA SNPs, are widely studied in AMD patients. While we did not find any statistical differences in VEGF-A serum levels between the exudative AMD patients and controls, we confirmed results from several other studies which included total AMD patients or only exudative AMD patients, consisting of 27 to 71 samples per group in different populations [53][54][55][56][57][58][59][60]. Further studies revealed significantly elevated VEGF-A levels in exudative AMD patients compared to controls [61,62].…”
Section: Discussionsupporting
confidence: 88%
“…Many proinflammatory cytokines, such as tumor necrosis factor (TNF)-α, IL-6, IL-1β, IL-8 and VEGF, have both angiogenic and proinflammatory activity [ 14 , 105 , 106 , 107 , 108 ]. All the previously mentioned cytokines have been also linked to development of AMD [ 14 , 105 , 109 , 110 , 111 , 112 , 113 ]. Upregulation of these factors activates the endothelial cells and promotes angiogenesis ( Figure 4 ).…”
Section: Angiogenesis and Inflammationmentioning
confidence: 99%
“…IL‐8 is a neutrophil‐recruiting chemokine that also induces angiogenesis and the generation of superoxide radicals (Matsushima et al., 2022). Interestingly, the levels of IL‐8 have been found to be increased in the serum samples obtained from wet AMD patients when compared to their age‐matched controls (Liukkonen et al., 2022). In agreement with these proposals, the present study highlights the role of IL‐8 in the pathogenesis of AMD.…”
Section: Discussionmentioning
confidence: 99%